Investigation of Beam Column Joint with Beam Weak in Shear under Monotonic Loading - Mounika, B; Poluraju, P (International Journal of Engineering and Technology, 2018)
Earthquake affected structures, mostly failure occur at beam column joints (BCJ). BCJs are categorized according to their geometrical grouping as Interior, Exterior, and Corner joints. Exterior beam column joint (i.e., terminating the beam on one of the column faces) was the most vulnerable one with respect to the plane of loading. The present study aims at ductility behaviour of exterior BCJ with conventional reinforcement using the code IS 456-2000 and with special confining reinforcement using the Code IS 13920-2016. Four number of beam-column joint specimens are considered in which the first one is detailed as per IS 456-2000, the second one as per IS 13920-2016 and the other two with 50% and 30% reduction of shear reinforcement was provided while compared with the first specimen. It is mainly to satisfy the strong column-weak beam concept as the main parameter. The test was carried out on the loading frame with hinged conditions to the column both ends, and the load is applied at the tip of the beam. The experimental studies are proven with an analytical study carried out by finite element model by using ANSYS and disparate parameters are assessed both experimentally and analytically.Â Â